TAFSIR TEKS KEAGAMAAN OLEH PEMUDA MUSLIM DI DESA PLAJAN JEPARA UNTUK MODERASI BERAGAMA - Nur Mahmudah; Abdullah Abdullah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2023)
Moderate reasoning in religion cannot be separated from the understanding of religious texts by its adherents. Youth are a strategic part of society who are expected to continue and maintain the values and traditions of religious moderation. The residents of Plajan Jepara village adhere to four religions, namely Islam, Hinduism, Christianity and Buddhism.  This article aims to describe the form of religious tolerance in Plajan village and explain the youth's understanding of religious texts that support good practices of religious moderation in Plajan village. The research was carried out in the form of field research with a qualitative approach that explored data from 10 respondents from Muhammadiyah and Nahdhatul Ulama.  This article concludes that the good practice of religious moderation in Plajan village is based on a number of things, namely a history of peace, mutual cooperation, acceptance of other parties and based on local culture. This practice of religious moderation is supported by the government and local religious leaders. These values influence youth leaders who strive to maintain the  peace  theology and mutual cooperation between religious believers. Religious texts are understood by young people as the embodiment of divine values which provide freedom of religion (lakum dinukum wa liyadin), respect for neighbors and relatives and mutual love for each other. Thus, understanding religious texts is directed at supporting the function of religion as a unifier. Membentuk nalar moderat dalam beragama tidak dapat dilepaskan dari pemahaman teks keagamaan oleh para pemeluknya. Pemuda merupakan bagian masyarakat strategis yang diharapkan menjadi pelanjut dan perawat nilai dan tradisi moderasi beragama. Penduduk desa Plajan Jepara  memeluk empat agama yaitu Islam, Hindu, Kristen dan Budha.  Artikel ini bertujuan untuk mendeskripsikan wujud toleransi beragama di desa Plajan dan menjelaskan pemahaman para pemuda atas teks keagamaan yang mendukung praktik baik moderasi beragama di desa Plajan. Penelitian dilakukan berjenis field research dengan pendekatan kualitatif yang menggali data dari responden berjumlah 10 orang dari unsur Muhammadiyah dan Nahdhatul Ulama.  Artikel ini menyimpulkan praktik baik moderasi beragama di desa Plajan dilatarbelakangi oleh sejumlah hal yaitu sejarah damai,  kegotongroyongan,  peneriman atas pihak lain dan berbasis budaya lokal. Praktik moderasi beragama ini didukung oleh pemerintah dan pemuka agama setempat. Nilai-nilai ini mempengaruhi para tokoh pemuda yang berupaya merawat filosofi damai dan gotong rotong antar pemeluk agama. Teks keagamaan dipahami oleh para pemuda sebagai pengejawantahan nilai-nilai ke-Tuhanan yang memberikan kebebasan beragama (lakum dinukum wa liyadin), penghormatan kepada tetangga dan kerabat serta saling mengasihi sesama. Dengan demikian, pemahaman teks keagamaan diarahkan unuk mendukung fungsi agama sebagai pemersatu.